Intramolecular carbenoid ylide forming reactions of 2-diazo-3-keto-4-phthalimidocarboxylic esters derived from methionine and cysteine - Enßle, Marc; Buck, Stefan; Werz, Roland; Maas, Gerhard (Beilstein Journal of Organic Chemistry, 2012)
Methionine, S-benzylcysteine and S-allylcysteine were converted into 2-diazo-3-oxo-4-phthalimidocarboxylic esters 8a–c in three steps. Upon rhodium-catalysed dediazoniation, two intramolecular carbenoid reactions competed, namely the formation of a cyclic sulfonium ylide and that of a six-ring carbonyl ylide. The S-methyl and S-benzyl ylides 12a and b could be isolated, while S-allyl ylide 12c underwent a [2,3]-sigmatropic rearrangement. The short-lived carbonyl ylides derived from methionine and S-benzylcysteine formed head-to-tail dimers by a [3 + 3]-cycloaddition and could be trapped with external dipolarophiles, while the S-allyl derivative 14c yielded the pentacyclic compound 17 by an intramolecular [3 + 2]-cycloaddition reaction.
Keywords: α-aminoacids; carbonyl ylides; cycloaddition; α-diazo-β-ketoesters; sulfonium ylides